Effectiveness of OH card-based group mental health education in improving mood and behavior in breast cancer patients - Wang, Zhaojun; Hu, Xiaoqing; Xu, Jiangang; Zhou, Jieyu; Ou, Xiaojing; Chen, Meihua (Frontiers in Public Health, 2025)
PurposePsychological disorders and different coping styles often occur after breast cancer (BC) diagnosis. The purpose of this study was to explore the effect of OH card on psychological status and coping styles of individuals with breast cancer.MethodsThis was a non-randomized trial in which 54 outpatients or inpatients with BC who were willing to be assessed using psychological scales, allocated to either the OH card intervention group (OHG) or the usual care group (CG). The OHG received 1 session of OH card therapy over 2 h. Participants completed assessments of anxiety and depressive symptoms and coping styles using the Hospital Anxiety and Depression Scale (HADS) and Simplified Coping Style Questionnaire (SCSQ) scales at baseline, month 1, 3 and 6 post-intervention. Data were analyzed using descriptive statistics, chi-squared test and repeated measures ANOVA.ResultsThe HADS score in the intervention group was lower than that of the control group by 2.296 (p<0.05) at 1 month post-intervention. The SCSQ-positive coping aspect of usual care group scores showed a downward trend, while the OH card intervention group scores showed an upward trend, with a significant difference between the two groups (p = 0.040), and the difference between the two groups was significant at 1, 3 and 6 months after the intervention (all p < 0.05).ConclusionThe results of our study suggest that OH card intervention may improve symptomatology of anxiety and depression among people with BC at month1, and promote positive behavior within 6 months. The OH card intervention has a potential role in the psychological rehabilitation of individuals with breast cancer and warrants further research.